Coral Meninas Cantoras de Porto Murtinho: um estudo do timbre nas inter-relações com as identidades culturais e a sociedade - Passos, Cristina Maria Albuquerque (2013)
This research aims at the investigation of the timbre in the interrelation of Cultural Identities with the Society, in a case study of Choir Meninas Cantoras de Porto Murtinho. Located at the border between Paraguay and Mato Grosso do Sul, Porto Murtinho is characterized by the contact of three cultures of different origins, which is materialized in the use of three languages. With an interdisciplinary approach, based on the cultural history of social sciences, of the voice and the singing, this research relates Music, Culture and Society. This work is founded on participant observation, with qualitative approach, comparing and presenting the singing of the girls before and after the vocal work as well as questionnaires and interviews with professionals, choir participants and community members. During the analysis it remains clear the feedback between the objects studied, tone, identities, culture, choir and society, and their representations, that promote changes in the lives of the girls. Out of this study emerges the importance of the relationship between tone and cultural identities.